1992
DOI: 10.4294/jpe1952.40.99
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Love Waves Observed by a Strong-Motion Array in the Tokyo Lowlands, Japan.

Abstract: In order to investigate the generation and propagation of Love waves recorded in the Tokyo lowlands, we analyzed array data obtained for six events that occurred around the Kanto district. From wavenumber analysis, the following conclusions are obtained.(1) Love waves are converted from direct S-waves at the edge of a sedimentary basin. The Hachiohji tectonic line is an especially important zone for the generation of Love waves. (2) Apparent velocities of Love waves for periods between 6 and 9 s are concordant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…However, the wave types and secondary source areas of these later arrivals could not be examined because no small aperture array observation was being made in the Mexico City valley at that time. Kinoshita et al (1992) detected Love waves with a period of 7s in the S later arrivals observed by a small aperture array in the Kanto basin located in central Honshu, Japan during shallow earthquakes. Phillips et al (1993) also detected Love waves with a period of 1 s in array data in the western Kanto basin during shallow earthquakes.…”
Section: Introductionmentioning
confidence: 89%
“…However, the wave types and secondary source areas of these later arrivals could not be examined because no small aperture array observation was being made in the Mexico City valley at that time. Kinoshita et al (1992) detected Love waves with a period of 7s in the S later arrivals observed by a small aperture array in the Kanto basin located in central Honshu, Japan during shallow earthquakes. Phillips et al (1993) also detected Love waves with a period of 1 s in array data in the western Kanto basin during shallow earthquakes.…”
Section: Introductionmentioning
confidence: 89%
“…By using these separation methods of the wavefields, we can classify the surface waves secondarily excited in the basin. Therefore, the methods may be applicable to the interpretation of the secondarily excited surface waves reported by Kinoshita et al (1992).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that surface waves are excited in sedimentary basins from the analysis of earthquake records (Kinoshita et al, 1992) and numerical simulations (Bard and Bouchon, 1980 a, b). In order to estimate the surface waves, it is necessary to calculate wavefields in a two-or three-dimensional heterogeneous elastic medium.…”
Section: Introductionmentioning
confidence: 99%
“…In the Kanto Basin, dispersing waves having a predominant period of 5 to 10 s with a large amplitude are observed clearly for shallow earthquakes occurring at the west or south-west of the basin. Kinoshita et al (1992) revealed that those waves were Love waves excited at the Hachioji tectonic line. In the Osaka Basin, a strong later phase having a predominant period of about 3 s with amplitude larger than S wave is seen in the later phases even for deep earthquakes (Hatayama et al, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…The seismograms observed in a basin have been investigated to evaluate the site effects of the basin by many researchers (e.g., Tanaka et al, 1979;Minamishima et al, 1986;Frankel et al, 1991;Kinoshita et al, 1992;Yamanaka et al, 1992;Hatayama et al, 1995). These studies have revealed that secondarily generated surface waves originating from body waves or surface waves, which were propagated from epicenters have been observed in the various basins.…”
Section: Introductionmentioning
confidence: 99%